Soil weed seed bank in the function of biodiversity - Saulić, Markola M (Acta herbologica, 2024)
The effect of intensive agricultural practises on weed composition is well described for the aboveground flora, but less research has been done on how the impact might affect the soil weed seed bank. For this reason, during three years (2014-2017), the soil was sampled and the number of weed seeds in the soil was estimated by eight different management systems: (i) monoculture of maize, winter wheat and soybean, (ii) 2-year crop rotation (maize - winter wheat) with and without application of mineral fertilizer, (iii) 3-year crop rotation (maize - winter wheat - soybean) with mineral fertilizer, with manure and without application of fertilizer. The estimated soil weed seed bank was used to calculate the α and β diversity indices and determine the diversity, richness and uniformity of the weed community. The diversity indices confirmed that the diversity of the weed community is influenced by the strategy of crop rotation and the type of fertilization, that in the monoculture of winter wheat the diversity, the number of dominant weed species and the uniformity od weed community are the lowest, while in the 3-year crop rotation with mineral fertilization it is the richest biodiversity and weed community uniformity